Mapping STEM implementation in biology learning in Indonesia: Models, educational levels, outcomes, and challenges through a systematic literature review - Maulana Khalil Azizy; Yanti Herlanti; Evi Muliyah (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2026)
Although systematic reviews of STEM (Science, Technology, Engineering, and Mathematics) implementation in Indonesia have been widely conducted, previous studies have mainly focused on learning outcomes in specific educational contexts. Comprehensive mapping of STEM implementation in biology learning in Indonesia remains limited. This study aims to analyse the implementation of STEM-based biology learning in Indonesia. It employs the Systematic Literature Review (SLR) method following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were sourced from publications indexed in Scopus and Google Scholar. The initial search identified 1,041 records covering biology, learning, and STEM. After applying the inclusion criteria, 77 articles on STEM-based biology learning published between 2015 and 2025 were selected as the final sample. The results indicate that Project-Based Learning (PjBL) (n=19) and Problem-Based Learning (PBL) (n=8) dominate the STEM models applied, while the STEM Engineering Design Process (STEM-EDP) (n=1) remains underrepresented. Implementation is concentrated in Java (n=40). Cognitive outcomes, such as critical thinking (n=19) and creative thinking (n=15), are more frequently reported than non-cognitive outcomes, such as motivation and scientific attitudes. The main challenges are teacher readiness (n=27), time constraints (n=8), and limited facilities (n=21), while student enthusiasm and the availability of learning materials serve as key supporting factors. The results have important implications for educational policymakers and biology educators, including promoting more equitable STEM integration, strengthening teacher professional development, and expanding the adoption of STEM-EDP approaches beyond Java. Future research should examine the effectiveness of underutilised STEM approaches, particularly STEM-EDP.